MISCHIEVOUS BEHAVIOR IN HONEY DEE’S NOVEL UNBROKEN VOW - Asri Audrylia Lufti; Safitri Hariani (JOURNAL OF LANGUAGE, 2022)
This study is entitled Antagonist’s Mischievous Behavior in Honey Dee’s novel Unbroken Vow. The story tells about the antagonist, Mirriam who comes from family trouble and she is full of jealousy when seeing someone who has a happy family. Mirriam has a desire to destroy the protagonist’s family by giving poison, injecting narcotics, making sexual abuse, and attacking everyone around her. The researchers are curious and interested in analyzing the antagonist's mischievous behavior because all the deeds are weird. The researchers also wish to know the reasons why the antagonist does such things. This article uses mischievous behavior theories by Purwanto and Denis. In completing the analysis, this study uses descriptive method proposed by Meoleong who describes the ways of conducting research method. The findings show that the types of mischievous behavior conducted by the antagonist are: attacking her rival, sexual abuse, injecting narcotics and giving poison; while the reasons of mischievous behavior are having problems at home, being bullied and having no clear boundaries.